Is one enough? The case for non-additive influences of visual features on crossmodal Stroop interference - Appelbaum, Lawrence G.; Donohue, Sarah E.; Park, Christina J.; Woldorff, Marty G. (Frontiers in Psychology, 2013)
When different perceptual signals arising from the same physical entity are integrated, they form a more reliable sensory estimate. When such repetitive sensory signals are pitted against other competing stimuli, such as in a Stroop Task, this redundancy may lead to stronger processing that biases behavior toward reporting the redundant stimuli. This bias would therefore, be expected to evoke greater incongruency effects than if these stimuli did not contain redundant sensory features. In the present paper we report that this is not the case for a set of three crossmodal, auditory-visual Stroop tasks. In these tasks participants attended to, and reported, either the visual or the auditory stimulus (in separate blocks) while ignoring the other, unattended modality. The visual component of these stimuli could be purely semantic (words), purely perceptual (colors), or the combination of both. Based on previous work showing enhanced crossmodal integration and visual search gains for redundantly coded stimuli, we had expected that relative to the single features, redundant visual features would have induced both greater visual distracter incongruency effects for attended auditory targets, and been less influenced by auditory distracters for attended visual targets. Overall, reaction times were faster for visual targets and were dominated by behavioral facilitation for the cross-modal interactions (relative to interference), but showed surprisingly little influence of visual feature redundancy. Post-hoc analyses revealed modest and trending evidence for possible increases in behavioral interference for redundant visual distracters on auditory targets, however, these effects were substantially smaller than anticipated and were not accompanied by a redundancy effect for behavioral facilitation or for attended visual targets.